IMPLEMENTASI KEBIJAKAN PENERIMAAN PESERTA DIDIK BARU (PPDB) SISTEM ZONASI SMP NEGERI DI KOTA BEKASI - Dewi, Religi Cipta; Subowo, Ari; Afrizal, Teuku (Journal of Public Policy and Management Review)
There are still several aspects that hinder the process of implementing the zoning system for the new Student Admissions policy in providing opportunities and access to education rights. The aim of this study was to describe the implementation of the PPDB policy on the zoning system of public junior high schools in Bekasi City and to identify the supporting and inhibiting factors. The research uses the Van Meter and Van Horn Policy Implementation theory by looking at policy standards and objectives, resources, inter-organizational relations, characteristics of implementing agents, socio-political economic conditions, and the disposition of implementors as variables that influence policy implementation. This research is descriptive qualitative with a case study approach. Data collection techniques were carried out by interview, observation, and literature study through primary and secondary data sources. The results showed that the implementation of this policy was in accordance with the applicable rules and stages. However, there are still errors in ordinate points, unequal distribution of facilities between schools, changing SOPs, and many people who are reluctant to choose private junior high schools. In conclusion, the implementation of this policy is supported by the standard variables and policy objectives, inter-organizational communication relations, and the disposition of the implementor. Meanwhile, the variables of resources, characteristics of implementing agents, and socio-political and economic conditions are obstacles. This study recommends optimizing data verification and leveling facilities between schools, involving all implementing agencies in setting Standard Operating Procedure, as well as optimizing the role of private junior high schools